Association of cesarean scar defect with abnormal uterine bleeding: The results of a prospective study. (January 2020) - Antila, Riitta M.; Mäenpää, Johanna U.; Huhtala, Heini S.; Tomás, Eija I.; Staff, Synnöve M.
Abstract: Objective: To evaluate the relationship between cesarean scar defect and abnormal uterine bleeding at one year after cesarean section (CS). Study design: A prospective observational cohort study was conducted in 401 women who delivered by CS between January 2016 and January 2017. Women were screened for isthmocele with sonohysterography six months after CS and followed by electronic questionnaires at 12, 13 and 14 months after CS. The main outcome measure was the prevalence of postmenstrual spotting. Secondary outcome measures were the duration of menstrual bleeding, prevalence of postcoital bleeding, dyspareunia or dysmenorrhea, usage of painkillers, and absence from work or other activities. Results: The response rate was 88 %. In the isthmocele group, the prevalence of postmenstrual spotting was 20.0 % compared to 8.3 % in women without isthmocele (OR 2.75 [95 % CI 1.39–5.44]; P = 0.004). Additionally, women with isthmocele reported more frequently postcoital bleeding (8.3 % vs. 2.4 %; OR 3.73 [95 % CI 1.18–11.83]; P = 0.026). The prevalence of postmenstrual spotting was even higher in the subgroup of large isthmoceles, (25.9 % vs. 9.5 %; (OR 3.34 [95 % CI 1.72–6.49]; P < 0.001). Conclusion: The prevalence of postmenstrual spotting among isthmocele patients was 20.0 %. Additionally, postmenstrual spotting was associated with the presence of isthmocele inquired at 1 year after CS.